On-the-job search and sorting - Pieter A. Gautier; Coen N. Teulings; Aico van Vuuren (Center for Economic Studies and ifo Institute (CESifo), 2005)
We characterize the equilibrium of a search model with a continuum of job and worker types, wage bargaining, free entry of vacancies and on-the-job search. The decentralized economy with monopsonistic wage setting yields too many vacancies and hence too low unemployment compared to first best. This is due to a business-stealing externality. Raising workers? bargaining power resolves this inefficiency. Unemployment benefits are a second best alternative to this policy. We establish simple relations between the losses in production due to search frictions and wage differentials on the one hand and unemployment on the other hand. Both can be used for empirical testing.
Keywords: J6; J3; 330; Arbeitsplatzsuchmodell; Lohnverhandlungen; Lohndifferenzierung; Theorie